Simultaneous Presentation of a Right Littre’s Hernia and a Left Amyand’s Hernia in a School-Aged Patient - Andrés Eduardo Velásquez-Bueso; Luis Enrique Sánchez-Sierra; Sergio David Villeda-Rodríguez; Roberto Antonio Martínez-Quiroz (Case Reports in Surgery)
Introduction. Inguinal hernia is the most common condition in both male and female subjects. Amyand’s hernia is characterized by the presence of the cecal appendix, swollen or not, inside the inguinal hernia sac. It is a rare condition and represents 1% of all the inguinal hernia pathology. Littre’s hernia (LH) is a condition defined by the presence of a Meckel diverticulum (MD) inside a hernial sac. It is an extremely rare condition, with less than 50 cases reported in the last three hundred years, present in only 1% of all diagnosed MD. Case Presentation. A six-year-old male patient presented with a history of two bilateral protruding masses in the inguinal-scrotal region that have continued to grow since birth. No gastrointestinal symptoms were reported. Physical examination showed a bilateral inguinoscrotal mass which increased in size during the Valsalva maneuver. Surgical intervention was carried out with a bilateral hernia repair being performed under an anterior method, the surgical invagination of the MD within the small intestine and the appendix within the caecum. Conclusion. Both entities should be considered as a differential diagnosis when it comes to a pediatric patient with unilateral or bilateral inguinal hernias with an uncertain etiology, allowing an early diagnosis and prompt treatment. We present here the first recorded case of both Amyand’s hernia and Littre’s hernia presenting simultaneously in a pediatric patient.